1098 Prophylactic Doxycycline Prior To The Excision of Ulcerated Skin Lesions. An Audit of Dose Timings and Adverse Effects. (12th October 2021) - Wallace, J; Gibson, J; Duncan, R
Abstract: Aim: Antibiotic prophylaxis to reduce the incidence of surgical site infections following excision of ulcerated skin lesions is frequently recommended, although the evidence base is limited. Current Swansea Bay guidelines recommend pre-operative administration of antibiotics: for procedures performed under local anaesthetic in the Plastic Surgery Treatment Centre (PSTC), oral route is preferable. It was noted that a number of patients were experiencing nausea and vomiting following administration of the recommended oral agent (doxycycline). The aim of this audit was to quantify the proportion of patients experiencing adverse effects, and to assess whether the prophylactic dose was being administered within the recommended time frame. Method: Data was collected over a three-week period (28/10/20- 18/11/20). All patients that received doxycycline pre-operatively during this period were included: the time the doxycycline was given, the time of operation and whether there were any adverse effects was recorded for each patient. Results: 14 patients received doxycycline during the monitored period. On average the doxycycline was given 52 minutes prior to the procedure. 2 patients received their doxycycline dose after their procedures. 4 patients experienced side effects from the doxycycline (3 vomited, 1 nausea), the average time this subset of patients received their dose was 50 minutes prior to their procedure. Conclusions: A significant proportion of patients experience adverse after receiving doxycycline, whilst there is limited evidence to prove its benefits. Trust guidelines are under review to consider alternative antibiotics, but better evidence is required to clarify the need for antibiotic prophylaxis for ulcerated lesions.